Tendencies in evaluation of portfolio investment - Zaliubovska, S. S.; Novikova, L. A. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Investment and related activities have considerable importance for assurance of sus-tained economic growth, institutional and structural modernization of the economy. Because of the pressures coming from current economic performance of Ukraine, caused by various kinds of risks, portfolio and venture investment still remain preferable options of financing. Foreign practices of joint investment show that the tools involved in joint investment institutes have been quite popular form used by potential investors. The objective of the study is to analyze methods involved in evaluation of portfolio investment with consideration to operative practices at the Ukrainian domestic market and respective international standards. Models for formation of optimal investment portfolio, their specifics and types are discussed. The review covers groups of models for investment portfolio formation, types of linear models for formation of optimal investment portfolio, methods used in multi-criteria model for investment portfolio formation, methodology for evaluation of investment portfolio by Global Investment Performance Standards. The conclusion is made that the analyzed methods for evaluation of investment portfolio performance allow for taking the final investment decision either by foreign investors or by the government, and for solving the problem of risk minimization in transactions related to long-term investment in optimal portfolios.